2018
DOI: 10.1016/j.ijsu.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nonalcoholic fatty liver disease following pancreatectomy for noninvasive intraductal papillary mucinous neoplasm

Abstract: Patients undergoing pancreatectomy for benign disease have a significant risk of developing NAFLD but the frequency is lower than previously reported in cohorts that included individuals with malignant disease. Highest risk was observed in individuals who underwent pancreaticoduodenectomy or developed pancreatic atrophy. Further investigations to define the mechanisms that promote steatosis and interventions to prevent subsequent morbidity from NAFLD are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…The mean age was 64.7 (SD AE 5.9) years, the sex relation M/F 1:0.8. Three studies 59,62,63 exclusively included patients with a benign tumor.…”
Section: Results Of Baseline Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age was 64.7 (SD AE 5.9) years, the sex relation M/F 1:0.8. Three studies 59,62,63 exclusively included patients with a benign tumor.…”
Section: Results Of Baseline Datamentioning
confidence: 99%
“…However, the first diagnosis of NAFLD was made during the first postoperative year in most patients. Three studies 59,62,63 reported development of NAFLD in 17.4% of patients with benign tumor, who underwent PD/PPPD exclusively. Studies with PD for predominantly malignant tumors reported NAFLD in 23.7% of patients.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Given that the cause of NAFLD is malnutrition, the lower incidence of NAFLD after DPPHR could be explained by the preservation of the duodenal and bile duct in the DPPHR group, thus preserving postoperative nutrition by maintaining normal gastroduodenal function and physiological bile secretion. Lue et al 26 revealed that the incidence of NAFLD is significantly lower in DP than in PD, even though the amount of resection of the pancreatic parenchyma is greater in DP than in PD. The absence of gastrointestinal reconstruction and preservation of the duodenum in DP may be essential for the low incidence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Luu et al showed that patients who underwent pancreatectomy for benign noninvasive intraductal papillary mucinous neoplasms had a lower risk of developing NAFLD compared with patients with malignant disease. PD and the development of pancreatic atrophy were identified as significant risk factors in this study [ 51 ]. A small retrospective cohort study found that newly emerging NAFLD only developed occasionally after pancreatic neuroendocrine tumor resection and was mainly observed in patients with recurrent diseases.…”
Section: Nafld Following Pancreatoduodenectomymentioning
confidence: 99%